Membrane Technology for Osmotic Power Generation by Pressure Retarded Osmosis - Chung, Tai-shung.; Wan, Chun Feng. (Milton : CRC Press LLC, 2020)
Osmotic energy can be effectively harvested through pressure retarded osmosis (PRO) which is the most widely investigated technology due to its greater efficiency and higher power density output and effective membranes are the heart of the PRO technology. This book will cover a broad range of topics, including PRO membranes, fouling, module fabrication, process design, process operation and maintenance. It summarizes the progress in PRO researches in the last decade, and points out the directions for future R&D and commercialization of PRO. It will be of great interest to membrane researcher, company and operators to understand and get insights into the state-of-the-art PRO technologies.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Membranes (Technology); Renewable energy sources -- Technological innovations; Power resources; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Material Science